Genocide: A Crime with Intent to Destroy in Whole or in Part - Md. Hasnath Kabir Fahim (Lex Publica, 2023)
Abstract. Like all other crimes, genocide has some common elements such as an actus reus and a corresponding mens rea. Moreover, another subjective element is also present in all crimes of genocide which is the “intent to destroy, in whole or in part, a […] group as such.” This is also referred to as “genocidal intent” and it indicates that the criminal liability of genocide does not merely rely on the completed result of the committed act but depends on the intention of the perpetrator to achieve. However, the threshold of this intention is not as high as the mens rea narrated in Article 30 of the ICC Statute. In addition, there is no requirement for the existence of any special extent of this intention. Indeed, Dolus eventualis is adequate to perform the actus reus as well as to establish the particular “intent to destroy […].” The theoretical criterion of The Draft Elements of Crimes is both inadmissible and unadvisable for limiting the criminal liability of genocide or the authority of the Court for trying such crimes Keywords: Genocide, Genocidal Intent, ICC Statute, Mens Rea, Holocaust Abstrak. Seperti semua kejahatan lainnya, genosida memiliki beberapa elemen umum seperti actus reus dan mens rea yang sesuai. Selain itu, unsur subyektif lainnya juga hadir dalam semua kejahatan genosida yaitu “niat untuk menghancurkan, seluruhnya atau sebagian, suatu […] kelompok itu sendiri.” Ini juga disebut sebagai “niat genosida” dan ini menunjukkan bahwa pertanggungjawaban pidana genosida tidak hanya bergantung pada hasil akhir dari tindakan yang dilakukan tetapi tergantung pada niat pelaku untuk mencapainya. Namun ambang batas niat ini tidak setinggi mens rea yang diriwayatkan dalam Pasal 30 Statuta ICC. Selain itu, tidak ada persyaratan untuk adanya tingkat khusus dari niat ini. Memang, Dolus eventualis cukup untuk melakukan actus reus serta untuk menetapkan niat untuk menghancurkan [...]” tertentu. Kriteria teoretis dari Rancangan Elemen Kejahatan tidak dapat diterima dan tidak disarankan untuk membatasi pertanggungjawaban pidana genosida atau otoritas Pengadilan untuk mengadili kejahatan semacam itu Kata kunci: Genosida, Niat Genosida, Statuta ICC, Mens Rea, Holocaust